Association of carcinoma of the gallbladder with typhoid carriage in a typhoid endemic area using nested PCR - Nath, Gopal; Singh, Yogesh Kumar; Kumar, Kailash; Gulati, Anil Kumar; Shukla, Vijay Kumar; Khanna, Ajay Kumar; Tripathi, Sunil Kumar; Jain, Ashok Kumar; Kumar, Mohan; Singh, Tej Bali (The Journal of Infection in Developing Countries, 2008)
Background: Although well studied the association between chronic typhoid carrier state and carcinoma of the gallbladder (CaGB) remains unproven.Methodology: The study was performed at a tertiary care medical center in North India and involved 52 patients with CaGB, 223 patients with benign gallbladder diseases, 508 healthy individuals and, 424 corpses. For the detection of Salmonella enterica serovar Typhi, hepatobiliary specimens were subjected to DNA extraction for specific nested- PCR amplification of the S. Typhi flagellin gene. Anti-Vi S. Typhi antibodies were detected in serum samples from patients by indirect haemagglutination.Results: Thirty five of the 52 (67.3%) CaGB patients were PCR-positive for the S. Typhi flagellin gene; significantly higher than for patients with benign gallbladder diseases (95/223, 42.6%; p<0.01) and corpses (35/424, 8.2%; p<0.001). The numbers of individuals that had significant anti-Vi antibody titres (≥160) in their serum were 20/52 (38.5%) for CaGB patients, 31/223 (13.9%) for patients with benign gallbladder diseases, and 47/508 (9.2%) for healthy individuals.Conclusions: Specific nested-PCR amplification of the S. Typhi flagellin gene in hepato-biliary specimens was more sensitive for detection of S. Typhi carriage than anti-Vi antibody titres in serum. The results demonstrate an association between typhoid carriage and gallbladder diseases, both CaGB and benign. S. Typhi specific immunosuppression is also suggested in patients with gallbladder diseases.